A computational method for the Hufnagel pseudocylindric map projection family. Issue 1 (2nd January 2017) - Jenny, Bernhard; Šavrič, Bojan; Strebe, Daniel R.
ABSTRACT: In 1989, Herbert Hufnagel introduced a mathematical model for a family of equal-area, pseudocylindric projections, which includes the Mollweide, Wagner IV, and Eckert IV projections as specializations. Hufnagel's contribution has received very little attention, and his projections are not available in any of the commonly used cartographic software packages. This article makes three contributions: The Hufnagel family is introduced to the English-speaking community; algorithms for computing the forward and reverse projections are presented; and the eight new projections proposed by Hufnagel are analyzed.